What is the evidence for systemic effects of intravitreal anti-VEGF agents, and should we be concerned?. (10th December 2013) - Avery, Robert L
Abstract : Anti-vascular endothelial growth factor (VEGF) therapy has revolutionised the treatment of retinal disease, and appears to be very safe. Nevertheless, there are several lines of evidence that imply that small doses of these agents could potentially have a systemic effect. The clinical significance of these systemic effects remains unclear, but further study is indicated.